Estudo químico de agrotóxicos em tecido vegetal por MALDI-MS - Crisóstomo, Sabrina Gabriceli (2023)
With the increase in agricultural activities, vegetables are increasingly subject to exposure to pesticides, such as insecticides and fungicides. Excessive use of these products during cultivation is an aggravating factor, causing harmful effects on health. In order to control the use involved in these materials and ensure food safety, the scientific community has carried out research and developed methods capable of elucidating the composition and distribution of these agents in vegetable samples. Conventional techniques, such as gas chromatography and liquid chromatography, have traditionally been used in studies in these segments. However, recent studies point to the great potential of using mass spectrometry techniques with laser desorption ionization (LDI-MS) and matrix-assisted laser desorption/ionization (MALDI-MS) sources for the analysis of plant tissues. In the latest studies published by the regulatory body in Brazil, the National Health Surveillance Agency (ANVISA), the involved use of pesticides in food was presented due to the high rate of Identificação of these substances, often above the established limit. Kale, a very common vegetable in the Brazilian population's diet, stood out in this survey, due to the unsatisfactory results related to the use of pesticides. In this sense, the present work developed a method for monitoring pesticides presented in cabbage leaves by direct analysis, using the LDI and MALDI techniques. To develop the method, the ten most detected pesticides in the last ANVISA survey for cabbage crops were monitored, namely: Carbendazine, Cyromazine, Chlorpyrifos, Clothianidin, Deltamethrin, Imidacloriprid, Lambda-Cialothrin, Methomyl, Tebuconazole Trifloxystrobin. The MALDI-MS source was optimized by varying the type of matrix (2,5-dihydroxybenzoic acid, (DHB), α-cyano-4-hydroxycinnamic acid (CHCA) and 2-mercaptobenzothiazole (MBT)), its concentration (from 0.025 at 1.00 mg mL-1) and application method, mixture or sandwich. The results suggest a better ionization efficiency of the MALDI(+)MS technique, when the DHB matrix is used in low concentrations, that is, 0.050 mg mL-1 , and when applied in the form of a mixture, making it possible to detect seven pesticides out of the ten trained with ICTs, in most cases, higher than 106 . This performance was demonstrated to be superior to the LDI(±)MS technique.